Factors Influencing Survival Rates of Pronghorn Fawns in Idaho - Panting, Brett R.; Gese, Eric M.; Conner, Mary M.; Bergen, Scott (DigitalCommons@University of Nebraska - Lincoln, 2021)
Pronghorn (Antilocapra americana) occur throughout western North America. In Idaho, USA, following intensive hunting to reduce crop depredations in the late 1980s, pronghorn populations have not rebounded to desired levels. Because neonatal survival in ungulates is one factor limiting population growth, we evaluated cause‐specific mortality and the influence of intrinsic and extrinsic factors on survival rates of 217 radio‐collared pronghorn fawns across 3 study areas in Idaho during 2015–2016. For intrinsic variables, we determined the sex and body mass index (BMI) for each fawn. For extrinsic variables, we determined the abundance of predators and alternate prey, estimated the normalized difference vegetation index (NDVI) for 1 month pre‐ and post‐parturition, and measured fecal nitrogen and diaminopimelic acid (DAPA). We considered NDVI as a measure of plant productivity, and fecal nitrogen and DAPA as possible proxies of diet quality. We predicted NDVI, fecal nitrogen, and DAPA would be positively related to the nutritional status of females and positively related to fawn survival. We used Program MARK with known fate models to estimate semi‐monthly survival rates of pronghorn fawns for the first 4 months post‐parturition. During both years, the leading cause of fawn mortality was coyote (Canis latrans) predation (58%), followed by unknown causes of mortality (18%), unknown predation (12%), predation by bobcats (Lynx rufus; 6%), predation by golden eagles (Aquila chrysaetos; 3%), and other (3%). Mean fawn survival for the 4 months post‐parturition across years and study sites was 0.42±0.04 (SE; range = 28–62%). The top survival model included BMI, lagomorph abundance, and DAPA and had a model weight of 83.3%. All 3 variables were positively related to pronghorn fawn survival. Because females with increased nutrition generally have heavier fawns, BMI was likely correlated to diet quality, which was supported by the positive relationship between DAPA and fawn survival. We hypothesize that high lagomorph ...